Chemical Reactor Modeling Multiphase Reactive Flows - Jakobsen, Hugo A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Chemical Reactor Modeling closes the gap between Chemical Reaction Engineering and Fluid Mechanics. It presents the fundamentals of the single-fluid and multi-fluid models for the analysis of single- and multiphase reactive flows in chemical reactors with a chemical reactor engineering rather than mathematical bias. The book discusses numerical methods for solving the resulting equations as well as the interplay between physical and numerical modes. It is organized in 12 chapters combining theoretical aspects and practical applications and covers some of the recent research in several areas of chemical reactor engineering. This book contains a survey of the modern literature in the field of chemical reactor modeling. The book is written by a Chemical Engineer for Chemical Process Engineers using the standard terminology of this community. It is intended for researchers and engineers who want to develop their own codes, or who are interested in a deeper insight into commercial CFD codes in order to derive consistent extensions and to overcome "black box" practice. It can also serve as a textbook and reference book for both students and practitioners.
Single Phase Flow -- Single Phase Flow -- Elementary Kinetic Theory of Gases -- Multiphase Flow -- Multiphase Flow -- Flows of Granular Materials -- Constitutive Equations -- Applications -- Chemical Reaction Engineering -- Agitation and Fluid Mixing Technology -- Bubble Column Reactors -- The Population Balance Equation -- Fluidized Bed Reactors -- Packed Bed Reactors -- Numerical Solution Methods -- Mathematical Theorems -- Equation of Change for Temperature for a Multicomponent System -- Trondheim Bubble Column Model.
Keywords: Fluid mechanics; Chemical engineering; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Fluid Dynamics; Industrial Chemistry/Chemical Engineering; Engineering Thermodynamics, Heat and Mass Transfer